Utility of Accelerometers to Measure Physical Activity in Children Attending an Obesity Treatment Intervention - Wendy Robertson; Sarah Stewart-Brown; Elizabeth Wilcock; Michelle Oldfield; Margaret Thorogood (Hindawi Limited, 2011)
Objectives. To investigate the use of accelerometers to monitor change in physical activity in a childhood obesity treatment intervention. Methods. 28 children aged 7-13 taking part in "Families for Health" were asked to wear an accelerometer (Actigraph) for 7-days, and complete an accompanying activity diary, at baseline, 3-months and 9-months. Interviews with 12 parents asked about research measurements. Results. Over 90% of children provided 4 days of accelerometer data, and around half of children provided 7 days. Adequately completed diaries were collected from 60% of children. Children partake in a wide range of physical activity which uniaxial monitors may undermonitor (cycling, nonmotorised scootering) or overmonitor (trampolining). Two different cutoffs (4 METS or 3200 counts⋅min-1) for minutes spent in moderate and vigorous physical activity (MVPA) yielded very different results, although reached the same conclusion regarding a lack of change in MVPA after the intervention. Some children were unwilling to wear accelerometers at school and during sport because they felt they put them at risk of stigma and bullying. Conclusion. Accelerometers are acceptable to a majority of children, although their use at school is problematic for some, but they may underestimate children's physical activity.